Ragaireacht - Eadie, Jimmy (Bloomsbury Publishing, 2024)
This article will explore and discuss how at night, our sonic perception shifts dramatically. It will ask what traditions and rituals we have developed for this unique experience and, more precisely, how in Irish Gaeilge we have a unique word for a person who loves the solitude of such a nocturnal listening experience – Ragaireacht Gaeilge is a Celtic language, believed to have originated as Indo-European. However, English has been widely spoken throughout Ireland for many centuries. As of 2020, only 5 per cent of the population speak Irish fluently and on a daily basis. There are three main Irish Gaelic dialects, which originate within three distinct geographic locations: Munster, Connacht and Ulster. The main difference between the three is pronunciation. We have several words for sound, each with a slightly different meaning and appropriate usage. Some have the diacritic mark called a fada or great accent. It indicates that the vowel is to be pronounced ‘long’.
A Sound Word Almanac
PUBLISHED
London